Determination of moment carrying capacity of sagae connection using different methods. (15th March 2018) - Jeong, Gi Young; Kong, Jin Hyuk; Lee, So Sun
Highlights: Initial stiffness, yield load, and yield displacement of sagae joint were determined. FEM model was developed for stress distributions and load carrying capacity of sagae connection. Different evaluation methods were used for characterizing moment carrying capacity of sagae joint. Ductility ratio of sagae joint was determined. Moment carrying capacity of different sizes of sagae joints made from different wood species was evaluated. Abstract: The goal of this study was to analyze the moment carrying capacity of sagae connections. Sagae connections have been used for connecting a column and two cross beams in timber frame buildings in South Korea. Reverse-cyclic loading was applied to measure the load and moment carrying capacities of the sagae connection. Yield load, yield moment, and ductility ratio of the sagae connections were evaluated using three methods. Stress distribution, failure behavior, and load carrying capacity of sagae connection were analyzed using finite element methods. The most critical failure behavior of sagae connection was found to be a split at the reentrant corner of the upper beam. Stress distributions from FEM showed the highest stress values of combination of longitudinal stress (σL ) and shear stress (τRT ) at the reentrant corner. The difference of load carrying capacity of sagae connection ranged from 1.68% to 20.54%. In general, initial stiffness, yield load, maximum load, yield moment, and maximum moment of sagae connection increased as the size increased. However, yield displacement, maximum displacement, and ductility ratio of sagae connection did not show a consistent trend with an increment of size.